2021
DOI: 10.1039/d1ce00205h
|View full text |Cite
|
Sign up to set email alerts
|

Surface oxygen vacancies of TiO2 nanorods by electron beam irradiation for efficient photoelectrochemical water splitting

Abstract: TiO2 nanorods with oxygen vacancies are produced via a facial, controllable and scalable high energy electron beam irradiation treatment, resulting in a remarkable enhancement of photocurrent density of about 85.4% at 1.23 VRHE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…26,27 The formation of Vo in TiO 2 can be realized by various methods, including thermal reduction, 10,28 anaerobic heating, 1,29,30 plasma treatment, 2,31 and so on. 32,33 It is reported that Vo is responsible for the visible light absorption 11,20,34 enabling TiO 2 to absorb more solar light. 25,35 In addition, Vo can trap the photogenerated electrons, 22,36 thereby inhibiting the recombination of photoexcited charge carriers to improve the photocatalytic activity of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 The formation of Vo in TiO 2 can be realized by various methods, including thermal reduction, 10,28 anaerobic heating, 1,29,30 plasma treatment, 2,31 and so on. 32,33 It is reported that Vo is responsible for the visible light absorption 11,20,34 enabling TiO 2 to absorb more solar light. 25,35 In addition, Vo can trap the photogenerated electrons, 22,36 thereby inhibiting the recombination of photoexcited charge carriers to improve the photocatalytic activity of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The formation of Vo in TiO 2 can be realized by various methods, including thermal reduction, , anaerobic heating, ,, plasma treatment, , and so on. , It is reported that Vo is responsible for the visible light absorption ,, enabling TiO 2 to absorb more solar light. , In addition, Vo can trap the photogenerated electrons, , thereby inhibiting the recombination of photoexcited charge carriers to improve the photocatalytic activity of TiO 2 . , However, in some cases, Vo acts as the recombination centers of the photogenerated charge carriers, , which attenuate the photocatalytic performance of TiO 2 . The role of Vo in regulating the photocatalytic performance of TiO 2 is controversial, which still worths more research efforts. ,, In our previous work, vacuum annealing of hydrothermally prepared TiO 2 washed with ethanol creates the Vo in TiO 2 without visible light absorption .…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials are tiny particles with size distribution less than 100 nm. In the last decades, various types of nanomaterials have attracted the attention of many researchers in photocatalysis (Pan et al, 2021), electrocatalysis (Zhang et al, 2021a), photoelectrocatalysis (Hu et al, 2020;Zhao et al, 2020;Huang et al, 2021), solar utilization (Jiang et al, 2020), heat management (Zhang et al, 2021b) and other fields because of their unique properties (Wang et al, 2019;He et al, 2020). Among the numerous materials, Au represents one well-studied type (Xu et al, 2016) with tunable shape (Zhu et al, 2015), structure (Ma et al, 2015), and composition (Jiang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…1b show two peaks centered at 529.3 and 531.8 eV which are associated with the lattice oxygen bonded to Ti metal (Ti–O) and hydroxyl groups chemisorbed on Ti ions (Ti–OH) to reimburse the charge site of oxygen vacancies ( V O ), respectively. 36 The peak intensity of Ti–OH obviously decreases when the deposition temperature increases from 400 to 600 °C, which indirectly indicates the suppressed V O formation at high temperature. This is verified by estimating the ratio of V O to lattice oxygen using Gaussian fitting on the Ti–OH and Ti–O peaks, 37,38 where the ratios of 1.03, 0.53 and 0.43 have been acquired for samples prepared at 400, 500 and 600 °C, respectively.…”
Section: Resultsmentioning
confidence: 93%